Analysis of linear and nonlinear mathematical models for beams, cables, columns and rods - Janse van Rensburg, N.F. (Nicolaas) (University of Pretoria, 2022)
Dissertation (MSc (Applied Mathematics))--University of Pretoria, 2021.